A stoichiometric terbium-europium dyad molecular thermometer: energy transfer properties. Issue 1 (December 2018) - Bao, Guochen; Wong, Ka-Leung; Jin, Dayong; Tanner, Peter
Abstract The optical thermometer has shown great promise for use in the fields of aeronautical engineering, environmental monitoring and medical diagnosis. Self-referencing lanthanide thermo-probes distinguish themselves because of their accuracy, calibration, photostability, and temporal dimension of signal. However, the use of conventional lanthanide-doped materials is limited by their poor reproducibility, random distance between energy transfer pairs and interference by energy migration, thereby restricting their utility. Herein, a strategy for synthesizing hetero-dinuclear complexes that comprise chemically similar lanthanides is introduced in which a pair of thermosensitive dinuclear complexes, cycTb-phEu and cycEu-phTb, were synthesized. Their structures were geometrically optimized with an internuclear distance of approximately 10.6Å. The sensitive linear temperature-dependent luminescent intensity ratios of europium and terbium emission over a wide temperature range (50–298K and 10–200K, respectively) and their temporal dimension responses indicate that both dinuclear complexes can act as excellent self-referencing thermometers. The energy transfer from Tb3+ to Eu3+ is thermally activated, with the most important pathway involving the7 F1 Eu3+ J -multiplet at room temperature. The energy transfer from the antenna to Eu3+ was simulated, and it was found that the most important ligand contributions to the rate come from transfers to the Eu3+ upper states rather than direct ligand–metal transfer to5 D1 or5 D0 . As the first molecular-based thermometer with clear validation of the metal ratio and a fixed distance between the metal pairs, these dinuclear complexes can be used as new materials for temperature sensing and can provide a new platform for understanding the energy transfer between lanthanide ions. Luminescent lanthanides for nano-scale optical thermometers A metal-organic complex developed by researchers in China and Australia could greatly improve the accuracy of molecular-scale luminescent thermometers. The ability to measure temperatures in nano-sized spaces, such as within the human body or on microchips, holds great appeal. This promising approach uses molecular frameworks containing lanthanide ions, which display luminescence that is strongly dependent on their temperature. Ka-Leung Wong at Hong Kong Baptist University and co-workers synthesized two complexes containing a single pair of terbium and europium. By smart design and architecting at molecular level, the team fixed two ions with different emission colors at a distance of 1.06 nm, enabling effective energy transfer between the two single emitters. The luminescence from each ion responds differently as the temperature changes. Hence accurate temperature measurement is achieved via comparison of the luminescence from each emitter.